2014
DOI: 10.5993/ajhb.38.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed Prediabetes among Food Insecure Adults

Abstract: Prediabetes screening appears warranted for food insecure men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…We identified seventeen peer-reviewed USA articles studying the association between FIS and diabetes (29,55,61,82,107,109,(111)(112)(113)(114)(115)(116)(137)(138)(139)(140). Of those manuscripts, twelve of them show a significant association (Table S2- patterns which may be difficult for FIS individuals (141).…”
Section: Diabetesmentioning
confidence: 99%
“…We identified seventeen peer-reviewed USA articles studying the association between FIS and diabetes (29,55,61,82,107,109,(111)(112)(113)(114)(115)(116)(137)(138)(139)(140). Of those manuscripts, twelve of them show a significant association (Table S2- patterns which may be difficult for FIS individuals (141).…”
Section: Diabetesmentioning
confidence: 99%
“…Pre-diabetes awareness reportedly varies with factors such as age, level of educational attainment, health insurance coverage, and food security (Li et al, 2013;Ding et al, 2014). Data from the National Health and Nutrition Examination Survey (NHANES) indicated that while the condition is common among American adults, with approximately one-third estimated to have pre-diabetes, only 11% were aware that they had the condition (Li et al, 2013).…”
Section: Predictors Of Pre-diabetesmentioning
confidence: 99%
“…A recent study by Ding et al 25 showed that food insecure men were more likely than food insecure women or food secure men to have undiagnosed pre-diabetes. The authors suggested that men and women in poverty have different coping strategies, and that men may have higher rates of chronic illness than the data show.…”
Section: Race Sex and Food Insecurity -Strings Et Almentioning
confidence: 99%